The Role of Board Creativity in The Innovative Transformation of Cooperatives: A Product and Service Perspective in Banjarmasin - Monry Fraick Nicky Gillian Ratumbuysang; Dasim Budimansyah; Dwi Atmono; Encep Syarif Nurdin (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the role of board creativity in driving cooperatives' innovative transformation, particularly in product and service development in Banjarmasin City. Using a mixed approach with an exploratory-consequential design, data were collected through a survey of 32 cooperative boards as well as in-depth interviews with 16 of them. The results show that board creativity-particularly in terms of openness to new experiences, ideation ability, and sensitivity to problems-contributes significantly to the creation of innovative cooperative products and services. However, there are constraints in the aspects of risk-taking, service quality, and member involvement in the innovative process. A Kirkpatrick model-based evaluation showed that the training designed significantly improved the creative capacity of the board. The study concludes that the integration of individual and collective creativity in cooperative governance is a key prerequisite for cooperative sustainability and competitiveness amid the dynamics of the digital economy and evolving member needs. The practical implications of these findings point to the urgency of strengthening innovative training systems, technological literacy, and data-based performance evaluation in cooperative management.